2010
DOI: 10.1007/s00774-009-0146-7
|View full text |Cite
|
Sign up to set email alerts
|

Mineral maturity and crystallinity index are distinct characteristics of bone mineral

Abstract: The purpose of this study was to test the hypothesis that mineral maturity and crystallinity index are two different characteristics of bone mineral. To this end, Fourier transform infrared microspectroscopy (FTIRM) was used. To test our hypothesis, synthetic apatites and human bone samples were used for the validation of the two parameters using FTIRM. Iliac crest samples from seven human controls and two with skeletal fluorosis were analyzed at the bone structural unit (BSU) level by FTIRM on sections 2-4 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(182 citation statements)
references
References 58 publications
13
166
0
3
Order By: Relevance
“…This finding could also be due to poorly organised apatite mineral that occurs during active bone remodelling. The findings reported here are consistent with those from a study by Farlay et al who also found that older bone had a higher crystallinity that new bone tissue [38]. The crystallinity of the bone material reported here is significantly higher when compared to hMSCs which are from the same origin [34].…”
Section: Univariate Peak Analysissupporting
confidence: 92%
“…This finding could also be due to poorly organised apatite mineral that occurs during active bone remodelling. The findings reported here are consistent with those from a study by Farlay et al who also found that older bone had a higher crystallinity that new bone tissue [38]. The crystallinity of the bone material reported here is significantly higher when compared to hMSCs which are from the same origin [34].…”
Section: Univariate Peak Analysissupporting
confidence: 92%
“…Investigation of the bone mineral, by qBEI and FTIR, revealed that neither the degree of mineralization nor the maturity of the mineral was affected by the Glp1r deletion. However, it is important to bear in mind that due to instrument limitations, we were not capable of investigating mineral crystallinity as proposed by Farlay et al (2010). On the other hand, the maturity of the collagen matrix, determined as the 1660:1690 cm K1 ratio, was significantly reduced.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, the apatite crystals comprise two different environments: a non-apatitic hydrated domain, containing diverse labile and reactive ions, surrounds a relatively inert and more stable apatitic domain ( Fig. 1) (Farlay et al, 2010). In the interface between these domains, labile anions (PO 4 3-, HPO 4 2-and CO 3 2-) and cations (Ca 2+, Mg 2+ ) are easily and reversibly exchangeable.…”
Section: Mineral Phasementioning
confidence: 99%
“…During maturation and growth of the mineral, the apatitic domain of the crystal increases whereas the hydrated layer decreases, due to continuous ionic exchange between these domains and the solution bath. Soluble charged groups of proteins (Pr) can also participate in the ionic equilibrium of the non-apatitic domain (adapted from Farlay et al, 2010).…”
Section: Organic Phasementioning
confidence: 99%